Report on the Incidence of Longer-Term Program Engagement. (Policy Papers; Policy Paper, 2006)
During the discussion of the conclusions of the Task Force on Prolonged Use of Fund Resources, the Executive Board requested semi annual reports on the incidence of Longer-Term Program Engagement (LTPE). This is the sixth such report which provides information through June 2006.